A influência do cinismo sobre a doutrina Aristotélica do Spoudaios exposta na ética a Nicômaco - Prudente, Mauro Godoy (2014)
This thesis argues that the doctrine of spoudaios presented in the Nicomachean Ethics received the influence of the homonymous doctrine elaborated by the Cynicism several decades before the writing of the treatise of Aristotle. As asserted by the Cynics, the Stagirite says that happiness is the prize of excellence of character and this is only achieved by the spoudaios who is the personification of the criterion of excellent desires and rational measure that makes virtuous the action. The other agents should follow the spoudaios in his conduct because he is the paradigm of the human character's excelence. Aristotle began his research in ethics under the influence of Platonism and modified their philosophical orientation when realize that the doctrine of his master would lead to unsolvable aporias when applied to human action. In the Nicomachean Ethics, following the Cynic perspective, Aristotle developed his doctrine of ethic virtue having in the spoudaios its central figure.